Infiniteness of the Number of Eigenvalues Embedded in the Essential Spectrum of a \(2×2\) Operator Matrix - Muminov, M.I.; Rasulov, T.H. (Eurasian Mathematical Journal, 2014)
In the present paper a \(2×2\) block operator matrix H is considered as a bounded self-adjoint operator in the direct sum of two Hilbert spaces. The structure of the essential spectrum of H is studied. Under some natural conditions the infiniteness of the number of eigenvalues is proved, located inside, in the gap or below the bottom of the essential spectrum of H.